Optimasi produksi diasilgliserol dari crude palm oil menggunakan lipase spesifik 1,3-gliserida dari Rhizopus oryzae TP-2 Optimation of diacylglycerol production from crude palm oil using specific lipase of 1,3-glyceride from Rhizopus oryzae TP-2 - . SUHARYANTO; . TRI-PANJI; Urip PERWITASARI (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2011)
AbstractModern lifestyle caused the increasing prevalence ofobesity that precedes degenerative disease such as coronarycardiovascular disease, hypercholesterolemia, stroke, anddiabetes mellitus. Use of healthy oil in the daily food diet couldreduce the risk of the disease. One of healthy oils that proved tobe useful for human health is diacylglycerol (DAG).Unfortunately, production of DAG in Indonesia is hampered bythe relatively high price of the lipase enzyme. To overcome theprovision of costly imported lipase in producing DAG, aresearch was conducted by employing crude extract of lipaseenzyme from an indigenous mold namely Rhizopus oryzaeTP-2. Crude extract of lipase enzyme from mycelium culturefiltrate was freeze dryed and used for crude palm oil (CPO)bioconversion through glycerolysis at various processcondition. The objective of this research was to determineoptimum variable of temperature, incubation time, amount ofsubstrate and pH in producing DAG from CPO using lipase ofR. oryzae TP-2. The reseach result showed that lipase fromR. oryzae TP-2 was proved to be specific at position of 1,3-glyceride as indicated by glycerolysis products i.e DAG/TAGratio 0.48 higher than that of FFA/TAG ratio 0.06. Optimumconditions for glycerolysis were at temperature 37 o C, pH 7,3 g of CPO substrate, and 18 hours of incubation time. DAGyield by this optimum condition reach as much as 20.76 % w/w.The lipase derived from this experiment produced DAG betterthan that of using imported commercially lipase enzyme ofRhizomucor meihei.AbstrakGaya hidup modern telah menyebabkan meningkatnyakasus kegemukan yang berdampak timbulnya berbagaipenyakit degeneratif seperti jantung koroner, hiper-kolesterolemia, stroke dan diabetes mellitus. Penggunaanminyak sehat (healthy oil) sebagai menu diet sehari-hari dapatmengurangi faktor risiko penyakit tersebut. Salah satu jenisminyak sehat yang terbukti berdampak positif pada kesehatanmanusia adalah diasilgliserol (DAG). Sayangnya, produksiDAG di Indonesia terkendala oleh mahalnya enzim lipasespesifik 1,3-gliserida yang masih harus diimpor. Untukmengatasi mahalnya enzim lipase impor dalam produksi DAGdari CPO, penelitian penggunaan ekstrak kasar lipase darikapang lokal Rhizopus oryzae TP-2 telah dilakukan. Ekstrakkasar lipase dari filtrat kultur miselium R. oryzae TP-2dikeringbekukan dan digunakan untuk biokonversi CPOmelalui proses gliserolisis pada berbagai kondisi reaksi.Penelitian bertujuan menetapkan peubah suhu, waktu, jumlahsubstrat dan pH optimum dalam produksi DAG menggunakanlipase dari R. oryzae TP-2. Hasil penelitian menunjukkanbahwa enzim lipase R. oryzae TP-2 bersifat spesifik1,3-gliserida yang ditunjukkan oleh nisbah DAG/TAG, yaitu0,48 lebih besar dari nisbah ALB/TAG yaitu sebesar 0,06.Kondisi optimum untuk gliserolisis CPO adalah waktu inkubasiselama 18 jam, suhu reaksi 37°C, jumlah substrat CPO 3 g, danpH reaksi 7. Hasil DAG pada kondisi optimum gliserolisisadalah 20,76 %. (b/b). Lipase R. oryzae TP-2 yang digunakandalam penelitian ini menghasilkan DAG lebih tinggi dari padalipase impor asal Rhizomucor meihei.